Pioneering Logistics Management for Martian Exploration - Paché, Gilles (Technium Social Sciences Journal, 2025)
This article explores the challenges and opportunities of space logistics, particularly in the context of transporting resources to Martian colonies. It addresses key issues such as cost, travel time, technological limitations, and the environmental impact of space operations. The originality of this analysis lies in its examination of interplanetary supply chains as a driver of new markets, transformative technologies, and the emergence of complex new geopolitical, economic, and ethical risks. The relevance of the topic is underscored by the ambitious vision of Elon Musk and his company SpaceX for the colonization of Mars, particularly considering the re-election of Donald Trump as President of the United States in 2024. These developments make the regulation of space resources, the associated ethical challenges, and the potential inequalities between nations and corporations more pressing than ever. The present contribution opens promising research avenues concerning the profound impact of interplanetary supply chains on global economic systems, the sustainability of extraterrestrial colonies, and the advanced technological solutions needed to tackle the monumental logistical challenges of such an endeavor.